Peningkatan Kemampuan Berbicara Siswa Menggunakan Metode Bermain Peran (Role Playing) Pada Teks Fiksi dan Nonfiksi Kelas VIII A SMPN 1 Barat - Sukur, Miftah Faried Amiem; Vivi Rulviana; Guyup Paminto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The purpose of this study was to describe the results of classroom action research related to improving students' speaking skills using the role playing method. This research was conducted on class VIII A students of SMPN 1 Barat with a total of 32 students. This study uses a research model from Kemmis and Mc. Taggart. The approach in this study uses a qualitative description. While the data collection technique was carried out using tests and non-tests in the form of observation widths. Analysis of the data for each cycle showed that in cycle 1 the completeness of the students only reached 71.85%, which means they had not reached the target of completeness. In addition, the non-test results showed that the increase in students' speaking skills using the role playing method in cycle 1 reached 53.14%. (Less) and increased in the second cycle to 90.64%. Keywords: Role playing; Speaking Skills; Fictional and Nonfictional Texts.